Use of Audio Devices to Increase Preventive Health Behavior during Dental Visits - Normaliza Ab Malik; Azlan Jaafar; Aws Hashim Ali; Rusyda Helma Mohd; Nor Ba’yah Abdul Kadir (Universitas Indonesia, 2024)
Indexed by WOS